Agile user experience design : a practitioner's guide to making it work - Brown, Diana DeMarco (Morgan Kaufmann, 2013)
Being able to fit design into the Agile software development processes is an important skill in today's market. There are many ways for a UX team to succeed (and fail) at being Agile. This book provides you with the tools you need to determine what Agile UX means for you. It includes practical examples and case studies, as well as real-life factors to consider while navigating the Agile UX waters. You'll learn about what contributes to your team's success, and which factors to consider when determining the best path for getting there. After reading this book, you'll have the knowledge to improve your software and product development with Agile processes quickly and easily. Includes hands on, real-world examples to illustrate the successes and common pitfalls of Agile UX. Introduces practical techniques that can be used on your next project. Details how to incorporate user experience design into your company's agile software/product process.